Technique for privacy preserving real-time vehicle tracking using 802.11p technology - Singh, Jaipal (ACM, 2011)
Intelligent Transportation Systems (ITS) use sensors to capture real-time information for managing road congestion and more efficient utilisation of road infrastructure by motorists. Due to privacy laws in Australia and other countries, the road transport authorities are only allowed to collect anonymous road usage data, thus limiting their real-time analysis of road usage. This paper proposes a novel vehicle tracking method using the new 802.11p technology for wireless access in vehicular environments for providing accurate data while preserving the privacy of the road user. The proposed architecture captures vehicle movements from the start of the journey to the destination without identifying the same vehicle on subsequent journeys. This gives accurate vehicle journey data that will be used to improvement travel times, road safety and lower fuel consumption for motorists.